2002
DOI: 10.1073/pnas.172290899
|View full text |Cite
|
Sign up to set email alerts
|

FAST CARS: Engineering a laser spectroscopic technique for rapid identification of bacterial spores

Abstract: Airborne contaminants, e.g., bacterial spores, are usually analyzed by time-consuming microscopic, chemical, and biological assays. Current research into real-time laser spectroscopic detectors of such contaminants is based on e.g., resonance fluorescence. The present approach derives from recent experiments in which atoms and molecules are prepared by one (or more) coherent laser(s) and probed by another set of lasers. However, generating and using maximally coherent oscillation in macromolecules having an en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
139
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(144 citation statements)
references
References 66 publications
2
139
1
Order By: Relevance
“…In [9] the use of adaptive techniques in FAST CARS is explored for an identification of related biological objects such as bacterial spores.…”
Section: Introductionmentioning
confidence: 99%
“…In [9] the use of adaptive techniques in FAST CARS is explored for an identification of related biological objects such as bacterial spores.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of bacteria for our CARS experiments is mostly driven by the necessity of fast remote detection and recognition of anthrax (1)(2)(3). In particular, we study Bacillus subtilis endospores, which resemble anthrax endospores, and are, unlike anthrax, harmless.…”
mentioning
confidence: 99%
“…1 shows microscopic images of B. subtilis endospores, obtained by regular and phase-contrast microscopy. As is well known, the calcium salt of 2,6-pyridinedicarboxylic acid [or dipicolinic acid (DPA)] is a major chemical component of bacterial endospores, accounting for Ͼ15% of its molecular weight (1). Recently, it was shown that the sensitivity of CARS spectroscopy is sufficient to allow discrimination of DPA against other similar molecules (4).…”
mentioning
confidence: 99%
“…The fact that this ratio is approximately equal for all three temperatures indicates that all the Raman transitions are excited with the same phase, as would be expected for near-transformlimited pulses. 8 The excitation of the Raman coherence is discussed in detail by Scully et al 9 For longer delay times, the CARS signal decays because the Raman coherences for the various transitions oscillate at slightly different frequencies, resulting in a decay of the initial macroscopic Raman polarization. At higher temperatures the N 2 population is spread over a greater range of rovibrational levels.…”
mentioning
confidence: 99%